Congenital haemolytic disease (haemolytic disease of the newborn): a study of 157 cases, with special reference to the morbid anatomy and morbid histology of the disease process and to the pathogenesis of kernicterus - Claireaux, Arthur Edward (The University of Edinburgh, 1949)
Congenital haemolytic disease is a disease complex which may easily be separated into three more or less distinct clinical entities. These are:

1. Hydrops foetalis. 2. Icterus gravis neonatorum. 3. Congenital haemolytic anaemia.